Peningkatan Kompetensi Digital Pendidik Melalui Pelatihan Artificial Intelligence (AI) PAUD Aba Percontohan Bojonegoro - Putri, Berliana Fairelia; Masniyah, Hannik; Rahmawati, Adelia; Septi Putri, Adinda Balqis; Ratu Keylla, Citra Puspita; Nisa, Khoirun; Susilo, Heryanto; Tri 'Ulya Qodriyati (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: Digital transformation in the education sector requires teachers to master the latest technology, including artificial intelligence (AI). Early childhood education as a basis for learning requires teachers who can adapt to technological advances in order to create innovative and interesting learning experiences for children. However, there are still many PAUD educators who have difficulty integrating digital technology into teaching and learning activities. To meet this need, PAUD ABA Perpilotan Bojonegoro in collaboration with Bojonegoro ICT Volunteers held a training on